C1 lateral mass screw insertion from the caudal–dorsal to the cranial–ventral direction as an alternate method for C1 fixation: A quantitative anatomical and morphometric evaluation. (August 2017) - Senoglu, Mehmet; Karadag, Ali; Kinali, Burak; Bozkurt, Baran; icke, Cigdem; Halacoglu Savran, Duygu; Middlebrooks, Erik H.
Highlights: Anatomical knowledge is essential for successful posterior C1 vertebrae fixation. Pre-operative planning with CT landmarks is essential for ideal surgical outcomes. The technique may have less complications and better strength over traditional routes. Abstract: Object: C1 lateral mass screw has been widely used for fixation of the upper cervical spine. However, traditional fixation methods are not without complication. Morphometric measurement of an alternative approach is conducted. Methods: Three-dimensional CT scans of the cervical spine obtained in 100 adults were evaluated, and key measurements were determined for screw entry points, trajectories, and screw lengths for placement of a C1 screw via this alternate approach. Additional measures were included to account for relevant anatomic variation, including the size of the dangerous lateral zone of the C1 entry point and depth of the atlantooccipital joint surface. Twenty dried atlantal specimens were evaluated to determine corresponding ex vivo measurements. Results: The mean maximum angle of medialization was 20.8° ± 2.8° (right) and 21.1° ± 2.8° (left), as measured in the axial CT images. Sagittal CT images show the mean maximum superior angulation was 24.7° ± 4.3° (right) and 24° ± 4.0° (left), and the mean minimum superior angulation was 13.6° ± 4.4° (right) and 13.6° ± 3.9° (left). The mean screw length within the lateral mass was 21.2 ± 1.9 mm (right) and 21.3 ± 2.0 mm (left). Given an additional 10–15 mm needed for rod adaptation, an ideal screw length of 30–35 mm was determined. Conclusion: The C1 insertion caudally from the C2 nerve root may become an alternate method. Preoperative consideration of the ideal screw insertion point, trajectory, and length are vital for safe and effective surgical intervention.